Clinical and molecular significance of the RNA m6A methyltransferase complex in prostate cancer - Lothion-Roy, Jennifer; Haigh, Daisy B.; Harris, Anna E.; Metzler, Veronika M.; Alsaleem, Mansour; Toss, Michael S.; Kariri, Yousif; Ntekim, Atara; Robinson, Brian D.; Khani, Francesca; Gudas, Lorraine J.; Allegrucci, Cinzia; et al. (Frontiers in Genetics, 2023)
N6-methyladenosine (m6A) is the most abundant internal mRNA modification and is dynamically regulated through distinct protein complexes that methylate, demethylate, and/or interpret the m6A modification. These proteins, and the m6A modification, are involved in the regulation of gene expression, RNA stability, splicing and translation. Given its role in these crucial processes, m6A has been implicated in many diseases, including in cancer development and progression. Prostate cancer (PCa) is the most commonly diagnosed non-cutaneous cancer in men and recent studies support a role for m6A in PCa. Despite this, the literature currently lacks an integrated analysis of the expression of key components of the m6A RNA methyltransferase complex, both in PCa patients and in well-established cell line models. For this reason, this study used immunohistochemistry and functional studies to investigate the mechanistic and clinical significance of the METTL3, METTL14, WTAP and CBLL1 components of the m6A methyltransferase complex in PCa specimens and cell lines. Expression of METTL3 and CBLL1, but not METTL14 and WTAP, was associated with poorer PCa patient outcomes. Expression of METTL3, METTL14, WTAP and CBLL1 was higher in PCa cells compared with non-malignant prostate cells, with the highest expression seen in castrate-sensitive, androgen-responsive PCa cells. Moreover, in PCa cell lines, expression of METTL3 and WTAP was found to be androgen-regulated. To investigate the mechanistic role(s) of the m6A methyltransferase complex in PCa cells, short hairpin RNA (shRNA)-mediated knockdown coupled with next generation sequencing was used to determine the transcriptome-wide roles of METTL3, the catalytic subunit of the m6A methyltransferase complex. Functional depletion of METTL3 resulted in upregulation of the androgen receptor (AR), together with 134 AR-regulated genes. METTL3 knockdown also resulted in altered splicing, and enrichment of cell cycle, DNA repair and metabolic pathways. Collectively, this study identified the functional and clinical significance of four essential m6A complex components in PCa patient specimens and cell lines for the first time. Further studies are now warranted to determine the potential therapeutic relevance of METTL3 inhibitors in development to treat leukaemia to benefit individuals with PCa.